Auricular acupressure for adverse events following immunization related to COVID-19 vaccine injection: study protocol for a multicenter, three-arm, blinded randomized controlled trial - Qinwei Fu; Hui Xie; Li Zhou; Xinrong Li; Yang Liu; Min Liu; Chaoyu Wang; Xiaocen Wang; Zhiqiao Wang; Jinfan Tang; Huan Xiao; Zhiyong Xiao; et al. (Trials, 2021)
Abstract Background Some pain, fatigue, and gastrointestinal adverse events were observed in potential association with injection of COVID-19 vaccines, while there was no preventive intervention for it. We aim to investigate the efficacy of auricular acupressure (AA) therapy in preventing and relieving AEFI after injection of COVID-19 vaccine. Methods The study design is a randomized, multicentre, three-arm controlled, single-blind trial. Participants meeting the inclusion criteria will be advertised and enrolled and assigned in the medical institutions randomly for post-injection observation. No less than 360 participants will be randomized into one of three groups: auricular acupressure group, sham auricular acupressure group, and wait-list group. Interventions will be performed immediately and will happen 4 to 5 times per day for 5 days. The primary clinical outcomes will be quality and quantity evaluation among participants who reported any AEFI and who reported local pain at injection site. Secondary outcomes will concern headache, muscle and (or) joint pain, fatigue, nausea, vomiting, diarrhoea, and other potential events. All the outcomes will be assessed at baseline and 1, 3, 5, 7, and 14 days after the injection. Both intention-to-treat and per-protocol analyses will be performed, with significance level determined as 5%. Discussion Results of this trial will help to clarify the value of auricular acupressure therapy in preventing and relieving overall and certain adverse events following immunization after injection of COVID-19 vaccine. Trial registration China Clinical Trial Registry (ChiCTR) ( ChiCTR2100043210 ). Registered on 8 February, 2021.